2013
DOI: 10.1002/anie.201207748
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydrogenation of Isoquinolinium Salts Catalyzed by Chiral Iridium Complexes: Direct Synthesis for Optically Active 1,2,3,4‐Tetrahydroisoquinolines

Abstract: ,4-Tetrahydroisoquinolines (THIQs), a class of highly important molecular skeletons abundant in natural alkaloids and biologically active compounds, are often used as key intermediates for the synthesis of pharmaceutical drugs and drug candidates.[1] To date, synthetic efforts have focused on introducing chirality at the C1 position with configurational integrity by employing the following synthetic methodologies:[2] 1) the formation of the six-membered ring through a Bischler-Napieralski cyclization/reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(41 citation statements)
references
References 92 publications
1
39
0
1
Order By: Relevance
“…1 Although the synthesis of such saturated N-heterocycles remains challenging, 2 recent advances including diastereoselective metalation/cross-coupling, 3 conjugate additions of dihydropyridinones, 4 hydrogenation of disubstituted pyridines 5 and cyclization methods 6 are bringing these once exotic building blocks into the mainstream. Unfortunately, most of the available methods for the preparation of multisubstituted N-heterocycles deliver racemic products and prospects for enantioselective approaches to many substitution patterns are limited.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although the synthesis of such saturated N-heterocycles remains challenging, 2 recent advances including diastereoselective metalation/cross-coupling, 3 conjugate additions of dihydropyridinones, 4 hydrogenation of disubstituted pyridines 5 and cyclization methods 6 are bringing these once exotic building blocks into the mainstream. Unfortunately, most of the available methods for the preparation of multisubstituted N-heterocycles deliver racemic products and prospects for enantioselective approaches to many substitution patterns are limited.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Such high enantioselectivity was considered ac onsequence of the chelating coordination of substrates.Atypically proposed intermediate in asymmetric hydrogenation of olefinic substrates bearing acoordinating amide group involves,1 )both the C = Cd ouble bond and the coordinating functional group,2 )a dihydride rhodium(III) species generated in situ by the reaction of ar hodium(I) precursor with H 2 . [10] Asymmetric hydrogenation of heteroaromatics,such as quinolinium salts, [11] quinoxalines, [12] isoquinolinium salts, [13] pyridinium salts, [14] and quinazolinium salts, [15] was accomplished with the latter.A ccordingly,w e envisioned that rhodium analogues could serve as efficient new catalyst precursors,t hat could provide monohydride rhodium(III) species capable of catalyzing the asymmetric hydrogenation of simple olefins.W efound that chiral chloride-bridged dinuclear rhodium(III) complexes proficiently catalyzed the asymmetric hydrogenation of simple olefins,a sw ell as allylic alcohols,a lkenylboranes,a nd unsaturated cyclic sulfones.We initially synthesized chloride-bridged dinuclear rhodium(III) complex (S)-1a,b earing (S)-BINAP,b ya dding 5equiv of HCl in diethyl ether to am ixture of [RhCl(cod)] 2 and 2.05 equiv of (S)-BINAP in toluene at room temperature (Scheme 1). [2b, 4, 7, 8] Aiming to develop arhodium(III) catalytic system, we focused our attention on monohydride rhodium(III) complexes.O ur research was based on the reported reactivity of ethene inserted into aR h À Hb ond of monohydride rhodium(III) complexes bearing dicyclohexyl(2-methoxyethyl)phosphine.…”
mentioning
confidence: 99%
“…[5] Thus,h ydrogenation of simple olefins with high enantioselectivity by chiral rhodium systems has remained challenging, [6] despite the tremendous advances in iridium-catalyzed asymmetric hydrogenation of unfunctionalized olefins.I nt his pioneering work, Pfaltz demonstrated the high catalytic performance of P, N-ligated iridium complexes. [10] Asymmetric hydrogenation of heteroaromatics,such as quinolinium salts, [11] quinoxalines, [12] isoquinolinium salts, [13] pyridinium salts, [14] and quinazolinium salts, [15] was accomplished with the latter.A ccordingly,w e envisioned that rhodium analogues could serve as efficient new catalyst precursors,t hat could provide monohydride rhodium(III) species capable of catalyzing the asymmetric hydrogenation of simple olefins.W efound that chiral chloride-bridged dinuclear rhodium(III) complexes proficiently catalyzed the asymmetric hydrogenation of simple olefins,a sw ell as allylic alcohols,a lkenylboranes,a nd unsaturated cyclic sulfones. [9] Previously,wedeveloped chloride-bridged dinuclear iridium complexes that dissociated into the corresponding mononuclear monohydride iridium(III) complexes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 In the course of our investigation, we found that salt formation of the substrate facilitated the asymmetric hydrogenation of isoquinolines with high enantioselectivity. 10 We achieved asymmetric hydrogenation of 1,3-disubstituted isoquinolinium salts to construct two stereocenters on a cyclic amine skeleton. Encouraged by this result, we examined the asymmetric hydrogenation of multisubstituted pyridine derivatives in which multiple stereogenic centers can be introduced to the piperidine skeleton in a single operation.…”
mentioning
confidence: 99%